A Comparative Study on Total Muscle Protein Content of Different Fish Species in Fresh and Smoked - Dried Condition and to Analyze their Banding Pattern through SDS- PAGE: Life Sciences-Zoology for better Disease Understanding - Dipika Doloi; Devajit Basumatari (International Journal of Life Science and Pharma Research, 2022)
Fish plays an important role in human nutrition. They are known to be a very healthy food item. They are excellent protein sources that also deliver various minerals and vitamins necessary for good health. Due to the high content of polyunsaturated fatty a cid, fish flesh and fish oil are beneficial in reducing the serum cholesterol. In addition to that, the special type of fatty acid, omega -3 polyunsaturated fatty acid, is recognized as an important component to prevent a number of coronary heart diseases. Fish proteins contain all the essential amino acids in the required proportion and hence have a high nutritional value, which contribute to their high biological value. In fresh fi sh muscles, the water content is strongly bound to the proteins and cannot be easily removed even under higher pressure. For the present study, three different fish species, Clarias batrachus (E1), Mystus tengara (E2) and Puntius ticto (E3) were taken to study their protein content and analyze the electrophoretic protein banding pattern for both fresh and smoked dried conditions. Pr otein extract was made from the muscle tissue of the fishes taken. The protein content was measured by Lowry’s method using BSA protein as standard. The optical density was measu red at 660nm. The electrophoretic protein banding patterns were determined using SDS-PAGE gel electrophoresis. The results showed that the total protein concentration of samples for fresh condition E1F, E2F and E3F was found to be 7.15±0.247 mg/ml, 7.20±0.224 mg/ml and 4.98±0.283 mg/ml respectively and for smoked dried condition E1D, E2D and E3D was 8.48±0.273 mg/ml, 8.31±0.222 mg/ml and 5.81±0.335 mg/ml respectively. The SDS-PAGE electrophoresis showed significant increase in the protein bands of three types of smoked dried fish samples when compared to fresh ones. Therefore, the percentage of protein content in selected smoked dried fishes was found more.